Daily Walking and the Risk of Incident Functional Limitation in Knee Osteoarthritis: An Observational Study1. Issue 9 (September 2014) - White, Daniel K.; Tudor‐Locke, Catrine; Zhang, Yuqing; Fielding, Roger; LaValley, Michael; Felson, David T.; Gross, K. Douglas; Nevitt, Michael C.; Lewis, Cora E.; Torner, James; Neogi, Tuhina
<x xml:space="preserve">Abstract</x> Objective Physical activity is recommended to mitigate functional limitations associated with knee osteoarthritis (OA). However, it is unclear whether walking on its own protects against the development of functional limitation. Methods Walking over 7 days was objectively measured as steps/day within a cohort of people with or at risk of knee OA from the Multicenter Osteoarthritis Study. Incident functional limitation over 2 years was defined by performance‐based (gait speed <1.0 meter/second) and self‐report (Western Ontario and McMaster Universities Osteoarthritis Index physical function score >28 of 68) measures. We evaluated the association of steps/day at baseline with developing functional limitation 2 years later by calculating risk ratios adjusted for potential confounders. The number of steps/day that best distinguished risk for developing functional limitation was estimated from the maximum distance from chance on receiver operating characteristic curves. Results Among 1, 788 participants (mean age 67 years, mean body mass index 31 kg/m2, 60% women), each additional 1, 000 steps/day was associated with a 16% and 18% reduction in incident functional limitation by performance‐based and self‐report measures, respectively. Walking <6, 000 and <5, 900 steps/day were the best thresholds to distinguish incident functional limitation by performance‐based (sensitivity 67.3%, specificity 71.8%) and self‐report (sensitivity 58.7%, specificity 68.9%) measures, respectively. Conclusion More walking was associated with less risk of functional limitation over 2 years. Walking >6, 000 steps/day provides a preliminary estimate of the level of walking activity to protect against developing functional limitation in people with or at risk of knee OA.